1993
DOI: 10.1038/ng0693-187
|View full text |Cite|
|
Sign up to set email alerts
|

Allelic loss of chromosome 1p36 in neuroblastoma is of preferential maternal origin and correlates with N–myc amplification

Abstract: Neuroblastomas frequently have deletions of chromosome 1p and amplification of the N-myc oncogene. We analysed 53 neuroblastomas for the N-myc copy number, loss of heterozygosity (LOH) of chromosome 1p36 and the parental origin of the lost alleles. Allelic loss of 1p36 was found in 15 tumours. All N-myc amplified tumours belonged to this subset. In 13/15 tumours with LOH of 1p36 the lost allele was of maternal origin. This non-random distribution implies that the two alleles of the putative neuroblastoma suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 21 publications
3
81
1
Order By: Relevance
“…Examples include rhabdomyosarcoma (maternal chromosome 11p15.5) (Scrable et al, 1989), neuroblastoma (maternal chromosome 1p36 or paternal chromosome 2) (Caron et al, 1993), and acute myeloblastic leukemia (paternal chromosome 7) (Katz et al, 1992). These observations suggest an involvement of imprinted genes in tumor-initiation or progression processes.…”
Section: Discussionmentioning
confidence: 94%
“…Examples include rhabdomyosarcoma (maternal chromosome 11p15.5) (Scrable et al, 1989), neuroblastoma (maternal chromosome 1p36 or paternal chromosome 2) (Caron et al, 1993), and acute myeloblastic leukemia (paternal chromosome 7) (Katz et al, 1992). These observations suggest an involvement of imprinted genes in tumor-initiation or progression processes.…”
Section: Discussionmentioning
confidence: 94%
“…To sustain growth of the most aggressive form of neuroblastoma, these MYCN-amplified neuroblastoma cells may acquire mechanisms that suppresses MIZ-1 expression. Because MIZ-1 resides in 1p36 and the deletion of this chromosomal region is associated with MYCN amplification (31,32), a copy of MIZ-1 is likely to be deleted in MYCNamplified neuroblastoma, resulting in low MIZ-1 expression in these tumors. It was therefore not surprising that MIZ-1 expression lost its prognostic significance in a two-variable Cox regression analysis against MYCN amplification (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent genetic abnormality reported to date is the deletion of the short arm of chromosome 1 (Brodeur et al, 1981;Gilbert et al, 1984). Recent investigations have reported that the frequency of loss of heterozygosity (LOH) in 1p ranged from 20 to 89% (Fong et al, 1989(Fong et al, , 1992Suzuki et al, 1989;Weith et al, 1989;Takayama et al, 1992;Caron et al, 1993Caron et al, , 1996Schleiermacher et al, 1994;Takeda et al, 1994;Martinsson et al, 1995), and two or more tumour suppressor genes have been thought to be located in chromosome 1p (Schleiermacher et al, 1994;Takeda et al, 1994;Caron et al, 1995;Cheng et al, 1995). However, the genes on chromosome 1 responsible for NB have not yet been reported.…”
mentioning
confidence: 99%